Statistical comparison of singles badminton matches at the London 2012 and Rio de Janeiro 2016 Olympic Games - Torres-Luque, G.; Blanca-Torres, J. C.; Cabello-Manrique, D.; Kondric, M. (Journal of Human Kinetics, 2020)
The aim of this study was to analyse statistical differences in men`s and women`s singles badminton competitions at the London and Rio Olympic Games. Forty-five matches (128 sets in total) played at the 2012 and 2016 Olympics in badminton were analysed. Variables related to the match (6) and each set (13) were determined. The results show the longest rally in sets 1 and 3, the biggest come back to win the game in set 2, and that the duration of set 3 for men was longer in Rio than in London. All of the women`s sets had longer duration, and the rally length and the number of strokes per rally was also longer in Rio versus London. In conclusion, the timing factors of badminton singles were dissimilar in London 2012 and Rio 2016 for both men and women. This information may help players and coaches manage different workout types or, more specifically, competition schedules that are adapted to suit modern badminton`s characteristics.